A novel OpenSees element for single curved surface sliding isolators. Issue 119 (April 2019) - Gandelli, E.; Penati, M.; Quaglini, V.; Lomiento, G.; Miglio, E.; Benzoni, G.M.
Abstract: The increasing use of curved surface sliding bearings as seismic isolators benefits from the improvement of analytical models that can accurately capture their experimental performance and enhance the predictive capability of nonlinear response history analyses. The mathematical formulation proposed in this paper aims at addressing the variability of the coefficient of friction based on experimental data that can be retrieved from prototype tests on Curved Surface Sliders. The formulation accounts for variation in the coefficient of friction with the instantaneous change of axial load and sliding velocity at the contact interface, and the accumulated heat due to cyclic motion; furthermore, it incorporates new features such as the static friction developed in the transition from the pre-sliding phase to the dynamic sliding condition. The proposed model has been coded in the object-oriented finite element software OpenSees by modifying the standard SingleFPSimple3d element that describes the force – displacement relationship of a bearing comprising one concave sliding surface and a spherical articulation. The main novelties of the new CSSBearing_BVNC element are inclusion of the static friction before the breakaway and degradation of kinetic friction induced by the heat developed during the motion of the articulated slider. The primary assumptions in the development of the friction model and the verification of the newly developed element are validated by agreement with available data. A case study helps to demonstrate the improved prediction capability of the new bearing element over its standard counterpart when applied to real situations, such as estimating a +50% increase in isolator displacement, superstructure drift and base shear demand under high intensity earthquakes, and possible non-activation of the sliding isolators under weak or medium intensity earthquakes. Highlights: A friction law accounting for the effects of axial load, velocity and heating is presented. Contribution of static friction before the breakaway is included in the model. The friction law is coded in an OpenSees element of concave surface sliding bearing. Comparative evaluation of the new bearing element is performed through a case study. A more accurate estimation of displacement and force demands is provided.